Research on the Feasibility and Risk Response Measures of the Second-hand Clothing and Apparel Trading Market from the Perspective of Pet Economy - Qin, Siyu; Xie, Wenpeng; Gao, Yule (International Journal of Social Sciences and Public Administration, 2025)
With the continuous rise in pet ownership and the vigorous development of the "pet economy," the consumer demand for pet clothing has grown significantly. However, the rapid replacement of pet clothing has increasingly raised concerns about resource waste and environmental issues. This paper focuses on the field of used pet clothing, analyzing its development context, current status, and potential value. Socially, the popularization of environmental protection concepts and the cost-effectiveness needs of young pet-owning groups provide a realistic foundation for the used pet clothing market. Economically, the second-hand trading model not only reduces consumer spending but also unlocks the economic value of idle resources. Industrially, recycling used pet clothing helps alleviate textile waste pollution and promotes the sustainable development of the "pet economy." The study identifies key challenges, including the lack of standardized appraisal systems, hygiene and safety concerns, and fragmented distribution channels. It proposes solutions such as establishing quality certification standards, improving cleaning and disinfection processes, and building specialized trading platforms to enhance the circulation efficiency and consumer trust in used pet clothing, thereby contributing to the construction of a green and low-carbon pet consumption ecosystem.